Contingent Valuation on Urban Trees in City of Kota Kinabalu, Sabah - Muhammad Azrul Hilmi; Andy R. Mojiol (e-VIBS, Faculty of Science and Natural Resources, 2017)
This paper explores the function of urban trees in the City of Kota Kinabalu by finding the perception of public in the City about the trees and using Contingent Valuation Method (CVM) to find the valuation of urban tree in the city. Willingness to Pay (WTP) was chosen to use in the research to find the economic valuation of urban trees in city of Kota Kinabalu. The payment vehicle in the questionnaire is respondent WTP on donation and the elicitation method is open-ended question. A total of 121 questionnaires were selected for analysis from 154 questionnaires that distributed throughout the research. The majority of respondent are happy with the trees number and the function of trees in the city. Meanwhile, majority of respondent are willing to pay (donation) for increasing the number of trees in the city based on RM 5.00 that elicited. From the maximum WTP that stated, only 64 of questionnaires were selected for estimation of WTP after calculated the weakness of CVM. The mean and median of the WTP is calculated using basic mathematical and the value for mean is RM 7.84, while for the median is RM 5.00. Then, maximum aggregate WTP is calculated based on OLS regression model, maximum aggregate WTP= -2.717+8.481 (NT)- 3.423(BG )+ 4.296 (PG)+0.926 (PD) is find out where initial WTP stated , races, transportation and education have relationship with the WTP respondents stated. Based on the model, the maximum value of WTP is RM 2.54. Then, the total economic value of urban trees in the area based on the valuation, is calculated, for mean is RM 3,629,629.92 , median is RM 2,314,815.00 and maximum aggregate value is RM 1,175,926.02. Using 2% of market interest rate, the present value of the urban trees is RM 1,086,373.87.